2018
DOI: 10.1021/acs.est.7b04848
|View full text |Cite
|
Sign up to set email alerts
|

Monochlorinated to Octachlorinated Polychlorinated Dibenzo-p-dioxin and Dibenzofuran Emissions in Sintering Fly Ash from Multiple-Field Electrostatic Precipitators

Abstract: Polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDD/F) emissions in fly ash from multiple-field electrostatic precipitators in different sized sintering plants were studied. The monochlorinated-trichlorinated and tetrachlorinated-octachlorinated PCDD/F concentrations were higher for small plants (90 m) than for medium (91-180 m) and large (>180 m) plants. The PCDD/F concentrations and less-chlorinated PCDD/F contributions to the total PCDD/F concentrations increased as the fly ash particle size decreased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…These results indicated that the uptake of PCDD/Fs by fly ash is obviously lower than that of activated carbon. To date, several reports have suggested that the uptake of PCDD/Fs by fly ash mainly originates form carbonous residue [39,40]. These reports agreed well with this paper (Figure 4f).…”
Section: Effects Of Operating Parameters On ∑Pcdd/fssupporting
confidence: 92%
“…These results indicated that the uptake of PCDD/Fs by fly ash is obviously lower than that of activated carbon. To date, several reports have suggested that the uptake of PCDD/Fs by fly ash mainly originates form carbonous residue [39,40]. These reports agreed well with this paper (Figure 4f).…”
Section: Effects Of Operating Parameters On ∑Pcdd/fssupporting
confidence: 92%
“…Although the small plants that closed represented 31.9% of all plants, they produced only 6.8% of iron and steel production in 2015 and mostly lacked control technologies (21.3% had SO2 controls and none had SO2 and NOX controls), such that their retirement led to much larger reductions in emissions than production capacity 30 . Of the large plants (that is, those producing >10 million tonnes of crude steel per year) that closed, all were older than 40 years, and half were older than 80 years; by virtue of their age, these plants also accounted for disproportionately large emissions relative to their production 31 . Meeting ULE standards will probably entail further retirements of smaller (that is, those producing <1 million tonnes of crude steel per year) and older plants (that is, those operating >80 years); we estimate that phasing out such plants will contribute 21.4%, 24.5% and 20.8% of reductions in PM, SO2 and NOX emissions, respectively (purple bars in Fig.…”
Section: Measures To Meet Strengthened Standardsmentioning
confidence: 99%
“…The analysis method of PCDD/Fs in CP samples was modified from the U.S. EPA Method 1613. However, the pretreatment method of PCDD/Fs is usually based on environmental samples and biological samples and are not applicable to CP samples. CPs are soluble in most organic solvents and have properties similar to PCDD/Fs, and the extraction of trace PCDD/Fs from the highly concentrated CP matrix is a challenge for analyzing PCDD/Fs from CP products. In this study, through screening various extractive methods and solvents, a mixture of dichloromethane and hexane (1:9, v/v; 50 mL) was used to remove some of the CP matrix finally.…”
Section: Methodsmentioning
confidence: 99%